Opposition to Pharmacist Contraception Services: Evidence for Rebuttal - Madeline Mitchell; Courtney Stauffenberg; Veronica Vernon; Cortney M. Mospan; Allie Jo Shipman; Sally Rafie (MDPI AG, 2020)
Pharmacist contraception services are growing across the United States. Several states have authorized pharmacists to prescribe contraception, and the interest in other states continues to grow. Opposition to these practices exists and centers on discussions related to safety, training, cost, and fragmentation of care. We review these arguments and provide evidence refuting these concerns. Pharmacist-prescribed contraception increases access to care, and patients express interest in utilizing this service at the pharmacy. Pharmacists follow evidence-based recommendations. Counseling on preventative services and referral to other providers is part of contraception care by pharmacists. Training programs have been developed to equip both pharmacy students and pharmacists with the knowledge, skills, and tools needed to successfully provide these services. This article can serve as a guide for pharmacists and advocates when discussing pharmacist-prescribed contraception with policymakers, patients, and other healthcare professionals.